2009
DOI: 10.1016/j.bbrc.2009.01.083
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum signal peptide peptidase is a promising drug target against blood stage malaria

Abstract: The resistance of malaria parasites to current anti-malarial drugs is an issue of major concern globally. Recently we identified a Plasmodium falciparum cell membrane aspartyl protease, which binds to erythrocyte band 3, and is involved in merozoite invasion. Here we report the complete primary structure of P. falciparum signal peptide peptidase (PfSPP), and demonstrate that it is essential for parasite invasion and growth in human erythrocytes. Gene silencing suggests that PfSPP may be essential for parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 17 publications
3
46
0
Order By: Relevance
“…3A). Initially, we envisioned that we would build this assay in P. falciparum; however, genetic tractability was severely limiting, and PfSPP is an essential gene, so perturbations to this protein are lethal to the organism (33). To circumvent this difficulty, we designed the assay in the budding yeast Saccharomyces cerevisiae because of the genetic manipulability of this system and because S. cerevisiae contains no PS orthologue (thus yielding lower potential background signal) and only a single SPP gene (rather than five as in mammalian cells).…”
Section: Spp Inhibitors Directly Block Pfspp Activity In Heterologousmentioning
confidence: 99%
“…3A). Initially, we envisioned that we would build this assay in P. falciparum; however, genetic tractability was severely limiting, and PfSPP is an essential gene, so perturbations to this protein are lethal to the organism (33). To circumvent this difficulty, we designed the assay in the budding yeast Saccharomyces cerevisiae because of the genetic manipulability of this system and because S. cerevisiae contains no PS orthologue (thus yielding lower potential background signal) and only a single SPP gene (rather than five as in mammalian cells).…”
Section: Spp Inhibitors Directly Block Pfspp Activity In Heterologousmentioning
confidence: 99%
“…Artemisinin and its derivatives may be our last line of drug defense, although recent reports have indicated signs of reduced effectiveness of artemisinin combination therapies (ACTs) (23,28). For the development of the next generation of antimalarial agents, new targets and pathways susceptible to interruption by chemotherapy need to be identified.The asexual intraerythrocytic stages of Plasmodium development are responsible for the clinical symptoms attributable to malaria, and most antimalarial drugs target these stages of the parasite's life cycle (15,30). Many laboratories have focused on the hydrolytic process of hemoglobin (Hb) digestion within the parasite's specialized digestive vacuole as a target for drug discovery (4,7,16,18,32).…”
mentioning
confidence: 99%
“…The asexual intraerythrocytic stages of Plasmodium development are responsible for the clinical symptoms attributable to malaria, and most antimalarial drugs target these stages of the parasite's life cycle (15,30). Many laboratories have focused on the hydrolytic process of hemoglobin (Hb) digestion within the parasite's specialized digestive vacuole as a target for drug discovery (4,7,16,18,32).…”
mentioning
confidence: 99%
“…Proteases have long been considered viable drug targets. Recent studies have identified a single gene encoded aspartic protease essential for parasite development and survival [2,3,4,5]. This enzyme termed Plasmodium falciparum signal peptide peptidase (PfSPP) may serve as a promising drug target; however, its precise cellular function and natural substrates are not yet known.…”
Section: Introductionmentioning
confidence: 99%